Discoid lupus erythematosus associated with chronic granulomatous disease - Ana Carolina de Almeida Figueiredo; Ana Luísa Matos; Joana Calvão; José Carlos Cardoso (PAGEPress Publications, 2023)
To the Editor, Chronic granulomatous disease (CGD) is a primary immunodeficiency disorder in which a reduced activity of nicotinamide dinucleotide phosphate (NAPDH) oxidase leads to defective reactive oxygen intermediates (ROS) and impairs intracellular killing of microorganisms. Patients have recurrent bacterial and fungal infections as well as granuloma formations, and have a higher risk of autoimmune and inflammatory disorders like lupus erythematosus.1 A 20-year-old caucasian male with a diagnosis of autosomal recessive CGD was referred to our hospital because of a pruritic photosensitive rash on the face and hands, present for more than a year. [...]